2016
DOI: 10.7554/elife.20357
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated cell divisions drive the outgrowth of the regenerating spinal cord in axolotls

Abstract: Axolotls are unique in their ability to regenerate the spinal cord. However, the mechanisms that underlie this phenomenon remain poorly understood. Previously, we showed that regenerating stem cells in the axolotl spinal cord revert to a molecular state resembling embryonic neuroepithelial cells and functionally acquire rapid proliferative divisions (Rodrigo Albors et al., 2015). Here, we refine the analysis of cell proliferation in space and time and identify a high-proliferation zone in the regenerating spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(99 citation statements)
references
References 27 publications
6
90
3
Order By: Relevance
“…Axolotls are still growing as adults and the PCNA labeling reflected that. There was no evidence of distinct zones of proliferation distinguishing intact stump cord and regenerating ependymal cell outgrowth in the adult, unlike the high PCNA labeling zone described by Rost et al (2016) for larval cord after tail amputation. Axolotl ependymal cells in the regenerative outgrowth were proliferative and Msi-1 positive ( Figures 8F , 11E,F ), but intact adult Axolotl cord ependymal cells were proliferative and Msi-1 negative ( Figures 8D , 11E ).…”
Section: Discussioncontrasting
confidence: 64%
“…Axolotls are still growing as adults and the PCNA labeling reflected that. There was no evidence of distinct zones of proliferation distinguishing intact stump cord and regenerating ependymal cell outgrowth in the adult, unlike the high PCNA labeling zone described by Rost et al (2016) for larval cord after tail amputation. Axolotl ependymal cells in the regenerative outgrowth were proliferative and Msi-1 positive ( Figures 8F , 11E,F ), but intact adult Axolotl cord ependymal cells were proliferative and Msi-1 negative ( Figures 8D , 11E ).…”
Section: Discussioncontrasting
confidence: 64%
“…This constant mitotic activity implies the replication of a genome 10 times larger than that of humans (3200 Mb), in a short time, each round of division. 6,16 The need to constantly duplicate such a large genome, increases also the mutational rate inherent to the replication process, activated metabolism and the fine-tuned regulation of factors that modulate proliferation. 17 As a sum of all these factors one interrogation emerges, how in A. mexicanum the fidelity in the mitotically inherited genetic information and genomic stability are maintained in blastema cells during regeneration?…”
Section: Cellular Contributions To Blastema Formationmentioning
confidence: 99%
“… Abstract Axolotls are uniquely able to resolve spinal cord injuries, but little is known about the mechanisms underlying spinal cord regeneration. We previously found that tail amputation leads to reactivation of a developmental-like program in spinal cord ependymal cells (Rodrigo Albors et al ., 2015), characterized by a high-proliferation zone emerging 4 days post-amputation (Rost et al ., 2016). What underlies this spatiotemporal pattern of cell proliferation, however, remained unknown.…”
mentioning
confidence: 99%